A subset of CD163+ macrophages displays mixed polarizations in discoid lupus skin. Issue 1 (December 2015) - Chong, Benjamin; Tseng, Lin-chiang; Hosler, Gregory; Teske, Noelle; Zhang, Song; Karp, David; Olsen, Nancy; Mohan, Chandra
Abstract Introduction Lesional skin of patients with discoid lupus erythematosus (DLE) contains macrophages, whose polarization has yet to be investigated. To test our hypothesis that M1 macrophages would be increased in DLE skin, we examined transcriptome alterations in immune cell gene expression and macrophage features in DLE and normal skin by using gene expression and histochemical approaches. Methods Gene expression of RNA from DLE lesional and normal control skin was compared by microarrays and quantitative real-time polymerase chain reaction (RT-PCR). Both skin groups were analyzed for CD163 expression by immunohistochemistry. Double immunofluorescence studies were performed to characterize protein expression of CD163+ macrophages. Results DLE skin had twice as many upregulated genes than downregulated genes compared with normal skin. Gene set enrichment analysis comparing differentially expressed genes in DLE and normal skin with previously published gene sets associated with M1 and M2 macrophages showed strong overlap between upregulated genes in DLE skin and M1 macrophages. Quantitative RT-PCR showed that several M1 macrophage-associated genes—e.g., chemokine (C-X-C motif) ligand 10 (CXCL10), chemokine (C-C motif) ligand 5 (CCL5), and signal transducer and activator of transcription 1 (STAT1)—had amplified mRNA levels in DLE skin. CD163+ macrophages were increased near the epidermal-dermal junction and perivascular areas in DLE skin compared with normal skin. However, double immunofluorescence studies of CD163+ macrophages revealed minor co-expression of M1 (CXCL10, tumor necrosis factor-alpha, and CD127) and M2 (CD209 and transforming growth factor-beta) macrophage-related proteins in DLE skin. Conclusion Whereas a subset of CD163+ macrophages displays mixed polarizations in DLE skin, other immune cells such as T cells can contribute to the expression of these macrophage-related genes.